2011
DOI: 10.1017/s1751731110001758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic merit for carcass weight, breed type and slaughter weight on performance and carcass traits of beef × dairy steers

Abstract: Crossbreeding of Holstein-Friesian dairy cows with both early maturing (e.g. Aberdeen Angus (AA)) and late maturing (e.g. Belgian Blue (BB)) beef breeds is commonly practised. In Ireland, genetic merit for growth rate of beef sires is expressed as expected progeny difference for carcass weight (EPD CWT ). The objective of this study was to compare the progeny of Holstein-Friesian cows, sired by AA and BB bulls of low (L) and high (H) EPD CWT for performance and carcass traits. A total of 118 spring-born male p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…The lack of difference in intramuscular fat concentration between feeding treatments supports the findings of Moloney et al (2008) and likely reflects the duration of the re-alimentation period. The higher intramuscular fat concentration in muscle from AN in the present study supports the findings of other studies for the same genotypes (Keane et al, 2011) and reflects the maturity of the AN breed compared to the BB breed.…”
Section: Chemical Composition Of Ltlsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of difference in intramuscular fat concentration between feeding treatments supports the findings of Moloney et al (2008) and likely reflects the duration of the re-alimentation period. The higher intramuscular fat concentration in muscle from AN in the present study supports the findings of other studies for the same genotypes (Keane et al, 2011) and reflects the maturity of the AN breed compared to the BB breed.…”
Section: Chemical Composition Of Ltlsupporting
confidence: 91%
“…The difference in redness between genotypes supports the findings of Keane et al (2011) and Cuvelier et al (2006a, b). However, Campion et al (2009) found no difference in redness between AN and BB genotypes Carotenoid consumption by cattle results in accumulation in adipose tissue and more yellow colour (for review, see Dunne et al, 2009).…”
Section: Double Muscled Animals Have a Greater Percentage Of White Musupporting
confidence: 89%
“…A number of studies to date have investigated the physical and physiological differences in animals varying in EPD cwt (Crews et al, 2004;Keane et al, 2011). In addition, Bernard et al (2009) examined the effects of genetic selection in favor of high muscle growth on global gene expression in muscle tissue of young Charolais bulls.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that intramuscular fat content of cattle and beef quality are influenced by factors of the production or processing system including the breed, sex, age, housing system, feeding, and pre-slaughter handling, but also the individual genetic background of an animal [18,19] (Figure 1). The impact of breed on suitability for meat production was reported by many authors, but it is difficult to pinpoint the best breed for beef production and it is unlikely that one breed will have all the desirable traits for survival, growth, and quality meat production [20,21,22]. Breeds differ in many aspects including degree of muscling, intramuscular fat content, meat aroma, juiciness, and tenderness.…”
Section: Effect Of Some Slaughter Value Factors On Meat Qualitymentioning
confidence: 99%